Dual-layer vermiculite nanosheet based hybrid film to suppress dendrite growth in lithium metal batteries - Xu, Xiang-Qun; Jiang, Feng-Ni; Yang, Shi-Jie; Xiao, Ye; Liu, He; Liu, Fangyang; Liu, Lei; Cheng, Xin-Bing (Journal of energy chemistry, 2022)
A dual-layer vermiculite nanosheet based hybrid film can achieve a dendrite-free lithium metal anode. [Display omitted] Lithium metal anode has become a favorable candidate for next-generation rechargeable batteries. However, the unstable interface between lithium metal and electrolyte leads to the growth of dendrites, resulting in the low Coulombic efficiency and even the safety concerns. Herein, a rigid-flexible dual-layer vermiculite nanosheet (VN) based organic-inorganic hybrid film on lithium metal anode is proposed to suppress dendrite growth and relieve volume fluctuations. The inner mechanically robust VN layer (3 μm thick) enhances the mechanical properties of the protective layer, while the outer polymer (4 μm thick) can enhance the flexibility of the hybrid layer. The Li | Li symmetric cell with protected lithium shows an extended life of over 670 h. The full cell with Li anode protected by dual-layer interface exhibits a better capacity retention of 80% after 174 cycles in comparison to bare Li anode with 94 cycles. This study provides a novel approach and a significant step towards prolonging lifespan of lithium metal batteries.